Web-Based And Mobile-Based Information System Of Accompanying Diplomas - Sitanggang , Alfina Tiurmida; Maulana, Fajar (Jurnal Komputer Indonesia (Ju-Komi), 2023)
A certificate accompanying a diploma is a document that contains information about academic achievements from higher education with a degree, so that it is hoped that it will produce quality graduate students who can be accepted in society and the world of work in the future. From the results of a survey by researchers, currently Pelita Indonesia tertiary institutions are still applying manual certificate companion certificates (SKPI). Therefore the researchers aim to help simplify the process of SKPI data by using web-based information system design and Android mobile. The design design model uses the Unifield Modeling Language (UML) and implements the Development Life Cycle System (SDLC). It is hoped that this application can help students and academics in processing SKPI.